IVM results are comparable and may have advantages over standard IVF - Ellenbogen, A. (Universa Press, 2014)
Retrieval of immature oocytes from unstimulated ovaries, followed by in vitro maturation (IVM) was originally proposed in order to avoid side effects of gonadotropin administration. The target is to eliminate or significantly reduce the risk of ovarian hyperstimulation syndrome (OHSS) in patients with polycystic ovary syndrome (PCOS), drug cost and burden on patients. This technology was also suggested in treatment of normo-ovulatory women, fertility preservation or infrequent conditions such as failure of oocytes to mature or repeated development of poor quality embryos. In this study we intended to examine the possibility that IVM results may be comparable to standard IVF. A PubMed database search from 1999-2013 was carried out for publications concerning the indications of IVM and study the possibility that IVM results may be comparable to standard IVF. In vitro maturation of the oocytes procedures obtained up to 35% clinical pregnancy rate in young women, comparable with in vitro fertilization (IVF) in many programs. The obstetric and perinatal outcomes of IVM cycles are comparable with IVF/ICSI cycles. In conclusion IVM may gradually replace IVF in certain cases, as the technique continues to develop and pregnancy rates continue to increase, being a promising and simple alternative approach to standard IVF in various indications.